Weaning induces changes in behavior and stress indicators in young New Zealand rabbits - Gharib, Heba S. A.; Abdel-Fattah, Azhar F.; Mohammed, Haiam A.; Abdel-Fattah, Doaa M. (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was carried out to investigate the influence of weaning on the abnormal behavior, behavioral problems and some stress indicators in young rabbits. Materials and methods: The study was conducted on seventy two New Zealand rabbit kits which were divided into two groups, one reared with their dams (unweaned rabbits) and the other group reared without their dams (weaned rabbits). Rabbits are reared on traditional wire net batteries. A scan sample technique was used during the observation period of the recorded traits. Rabbits behavior was observed three times per day at (from 8.00 to 9.00 h), (from 12.00 to 13.00 h) and (from 15.00 : 16.00 h) for three days weekly to each group during the experimental period (6 weeks). The observed activities were recorded at 10 min interval for rabbits in each subgroup (6 subgroups for each group). Two blood samplings were taken after weaning process for monitoring some stress indicators. Results: The results showed that the bare biting and lixite bite were significantly affected by weaning which were increased in the weaned group than the unweaned group. Other abnormal behavioral traits and behavioral problems were not influenced by weaning process. The results found that cortisol, growth hormone levels, superoxide dismutase and catalase enzyme activities were significantly increased in serum after weaning. Conclusion: The weaning process has negative effect on some behavioral and physiological responses. So, rearing the young rabbits with their mothers is advantageous from the viewpoint of animal welfare. The findings of this study may help to find out suitable strategies to minimize post weaning stress in both human beings and domestic animals. http://doi.org/10.5455/javar.2018.e262